Performance of Millets in Bundelkhand Region of UP State (Indian Journal of Extension Education, 2021)
Time series data on area, production and productivity of major millets (2000-01 to 2019-20) was analyzed for Bundelkhand region of Uttar Pradesh state. Sorghum was the most important millet crop that accounted for highest area (36.6%) and (34%) of total millet area and production in UP state, respectively. Chitrakoot district contributed highest area (31.6%) under millets. Among all the millets, pearl millet recorded highest growth rate in area (0.97%), production (3.57%) and productivity (1.59%) with low instability index for area. The overall area and production of millet crops recorded decline in all the seven districts of Bundelkhand region during overall study period (2000-20). Lalitpur district recorded highest decline in area (-22.02%), followed by Chitrakoot (-10.82%) and Jhansi district (-10.63%) during overall study period, while during the same period Banda district recorded a growth in area (1.16%) and production (4.77 %) of pearl millet. The overall area, production and productivity of millets registered a decline in Bundelkhand region during 2000-20. This calls for aggressive promotional activities for enhancing millets production in the region.